2022
DOI: 10.1177/17085381211068228
|View full text |Cite
|
Sign up to set email alerts
|

An interesting finding: What is the relation between aortic enlargement and COVID-19?

Abstract: Background We aim to compare the diameters of ascending aorta in COVID-19 patients and COVID–19-free individuals referred to our pandemic hospital. Methods The medical records and thorax tomographies of patients admitted to the “pandemic central” state hospital with symptoms of COVID-19 were observed between April 2020 and May 2020 in this case-control study. The first group consisted of patients diagnosed with COVID-19, and the second group consisted of patients without the disease. The diameter of the ascend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Comparison of comorbidities based on the places of follow-up did not reveal any signi cant differences in terms of HT, DM, and heart disease. A study conducted with COVID-19 patients in Türkiye also reported hypertension (34.6%) as the most observed comorbidity, followed by diabetes mellitus (28.8%) and heart disease (13.5%), which is consistent with our study results (12).…”
Section: Discussionsupporting
confidence: 92%
“…Comparison of comorbidities based on the places of follow-up did not reveal any signi cant differences in terms of HT, DM, and heart disease. A study conducted with COVID-19 patients in Türkiye also reported hypertension (34.6%) as the most observed comorbidity, followed by diabetes mellitus (28.8%) and heart disease (13.5%), which is consistent with our study results (12).…”
Section: Discussionsupporting
confidence: 92%
“…We agree that CO-VID-19 may produce vascular abnormalities and that aortic elasticity may change as a result of COVID-19. Aortic enlargement and COVID-19 were also described in a recent publication [2]. However, in the context of the current report, there is a lack of data on the pre-CO-VID-19 vascular/health state of the subjects, making a final conclusion impossible.…”
mentioning
confidence: 59%
“…In the paper “Evaluation of Aortic Elasticity Parameters in Survivors of COVID-19 Using Echocardiography Imaging,” Küçük et al [ 1 ] mentioned that “ SARS-CoV-2 may cause reduced or impaired aortic elasticity parameters linked to impaired arterial wall function in COVID-19 survivors compared with controls .” We agree that COVID-19 may produce vascular abnormalities and that aortic elasticity may change as a result of COVID-19. Aortic enlargement and COVID-19 were also described in a recent publication [ 2 ]. However, in the context of the current report, there is a lack of data on the pre-CO­VID-19 vascular/health state of the subjects, making a final conclusion impossible.…”
mentioning
confidence: 97%
“…Bitargil et al mentioned that "the mean aortic diameter of COVID-19 patients is larger than non-COVID-19 patients with similar comorbidities referred to a pandemic …… COVID-19 was the leading factor. 1 " We agree that COVID-19 might have some clinical effects on vascular system. If COVID-19 results in enlargement of aorta, the pathological process should be acute process that the change can be detected in a short period of infection.…”
mentioning
confidence: 91%
“…Dear Editor, we would like to share ideas on the publication “An interesting finding: What is the relation between aortic enlargement and COVID-19? 1 ” In the present study, medical records and thorax tomographies of patients were analyzed. Bitargil et al mentioned that “ the mean aortic diameter of COVID-19 patients is larger than non–COVID-19 patients with similar comorbidities referred to a pandemic …… COVID-19 was the leading factor.…”
mentioning
confidence: 99%